Crack modes and toughening mechanism of a bioinspired helicoidal recursive composite with nonlinear recursive rotation angle-based layups. (June 2023) - Wang, Ke; Wu, Xiaodong; An, Lianhao; Li, Runzhi; Li, Zhiqiang; Li, Guoqiang; Zhou, Zhihui
Abstract: The rotation angle is an important parameter affecting the performance of helical structures, and helical structures with nonlinearly increasing rotation angles have been studied. The fracture behavior of a 3D-printed helicoidal recursive (HR) composite with nonlinear rotation angle-based layups was investigated by performing quasistatic three-point bending experiments and simulations. First, the crack propagation paths during the loading of the samples were observed, and the critical deformation displacements and fracture toughness were calculated. It was found that the crack path that propagated along the soft phase increased the critical failure displacement and toughness of the samples. Then, the deformation and interlayer stress distribution of the helical structure under static loading were obtained by finite element simulation. The results showed that the variation in the rotation angle between the layers caused different degrees of shear deformation at the interface between adjacent layers, resulting in different shear stress distributions and thus different crack modes of the HR structures. The mixed-mode I + II cracks induced crack deflection, which slowed the eventual failure of the sample and improved the fracture toughness. Highlights: The crack modes and toughening mechanism of 3D-printed helicoidal recursive composite were investigated. The interlayer rotation angle affects the way cracks initiate and propagate. The mixed-mode (i.e. mode I + II) crack induces the crack deflection. The recursive coefficient of the HR structure influenced the stress distribution and thus the final damage form.